2012
DOI: 10.1371/journal.pone.0037046
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Programs Controlling Perinatal Lung Maturation

Abstract: The timing of lung maturation is controlled precisely by complex genetic and cellular programs. Lung immaturity following preterm birth frequently results in Respiratory Distress Syndrome (RDS) and Broncho-Pulmonary Dysplasia (BPD), which are leading causes of mortality and morbidity in preterm infants. Mechanisms synchronizing gestational length and lung maturation remain to be elucidated. In this study, we designed a genome-wide mRNA expression time-course study from E15.5 to Postnatal Day 0 (PN0) using lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
71
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 96 publications
(122 reference statements)
8
71
1
6
Order By: Relevance
“…Many of the signaling and transcriptional mechanisms regulating early lung branching remain highly active in late gestation as the fetal lung undergoes sacculation, and airway epithelial cells differentiate to produce pulmonary surfactant (16). During the canalicular, saccular, and alveolar periods of lung morphogenesis, pulmonary mesenchymal cells differentiate to form fibroblasts, lipofibroblasts, pericytes, matrix-associated fibroblasts, smooth muscle, and endothelial cells in the distal lung.…”
Section: Transition To Air Breathing/pulmonary Maturationmentioning
confidence: 99%
“…Many of the signaling and transcriptional mechanisms regulating early lung branching remain highly active in late gestation as the fetal lung undergoes sacculation, and airway epithelial cells differentiate to produce pulmonary surfactant (16). During the canalicular, saccular, and alveolar periods of lung morphogenesis, pulmonary mesenchymal cells differentiate to form fibroblasts, lipofibroblasts, pericytes, matrix-associated fibroblasts, smooth muscle, and endothelial cells in the distal lung.…”
Section: Transition To Air Breathing/pulmonary Maturationmentioning
confidence: 99%
“…We have previously used genome-wide gene expression profiling to describe characteristic lung development genes in a small set of human lung samples (6). Similarly, animal studies performed by us and others have shown the validity of this approach to identify the key regulators of fetal lung development (6,7). Elucidating these genomic contributions to lung development will help determine molecular pathways involved in the development of lung disease and identify potential therapeutic targets.…”
mentioning
confidence: 99%
“…Bioinformatic analysis of lung RNA expression array data obtained after gene targeting or mutation of these critical transcription factors demonstrated their importance in perinatal lung maturation and surfactant synthesis(10-12, 15, 16). As a critical regulator of perinatal lung maturation, NKX2-1 is predicted to function with other transcription factors, e.g., HOPX, ETV5, GATA6, GRHL, FOXP2, and HMGA2, that together regulate many aspects of lung maturation, including alveolar type I/type II cell differentiation and surfactant synthesis(12). The direct binding of TTF-1 to cis-acting regulatory sites on target genes was identified by genome wide CHromatin ImmunoPrecipitation (CHIP) assays(17,18) demonstrating its binding to sequences in the ABCA3, SFTPA, SFTPB, and SFTPC genes.…”
mentioning
confidence: 99%